Return to Work in Patients with Acute Coronary Syndrome - Deddy Tedjasukmana (Indonesian Journal of Physical Medicine & Rehabilitation, 2017)
Acute coronary syndrome (ACS) is a medical term used to describe problems that occur when there isn’tenough blood flow to the heart, can lead to chronic heart disease (CHD). In Indonesia, 17.3 million deaths werecaused by CHD in 2008, it can be increased to 23.3 million deaths in 2030. A recent study states that ACS wasincreased among worker age. Therefore, the ability to return to work is important, because it can impact on theeconomic status of patients and their families, the patients’ quality of life, and also psychosocial factors.Patients who are hospitalized due to coronary heart disease need to have a cardiac rehabilitation program thatis divided into three phases. The patients are given a program that suits with their individual risk stratificationto achieve their vocational needs. The ability to work, work risk, work capacity, and work tolerance needs toevaluated by exercise test.After a comprehensive evaluation of coronary patients, it is important to determine suitability for work. Ingeneral, post-Percutaneous Coronary Intervention (PCI) ACS can return to previous jobs with some adjustmentsif needed. Energy expenditure monitoring during working can be measured by indirect and direct measurements.Keywords: Acute Coronary Syndrome, Cardiac Rehabilitation, Return to Work, Coronary Heart Disease.